Large bandgap observed on the surfaces of EuZn2As2 single crystals - Dejia Kong; Siavash Karbasizadeh; Ganesh Narasimha; Paras Regmi; Chenggang Tao; Sai Mu; Rama Vasudevan; Ian Harrison; Rongying Jin; Zheng Gai (Communications Physics)
Abstract EuM2As2 (M = Zn, Cd, In, Sn etc.) is an excellent material system for studying magnetism-tuned topological properties. However, discrepancies exist between experimental data and theoretical calculations regarding the bulk and surface bandgaps. In this work, cleaved EuZn2As2 crystals are studied using scanning tunneling microscopy/spectroscopy and density functional theory calculations. Triangular-shaped defect-induced modifications in the local density of states help distinguish between Eu-terminated and AsZn-terminated surfaces. While large bandgaps ( ~1.5 eV at 77 K) are observed on both pristine surfaces, the bandgap size is found to be highly sensitive to local heterogeneity, tending to decrease. By combining experimental observations with theoretical simulations, we conclude that the reduced bandgap in heterogeneous regions arises from Zn vacancies and/or substitution by As atoms, both impacting greater in the Eu surface electronic properties than those in the AsZn surface. This demonstrates the intimate relationship between the electronic structure and magnetism in EuZn2As2.